Peningkatan Minat Belajar Seni Tari Melalui Penerapan Pendekatan Cooperative learning Tipe Jigsaw Dalam Pembelajaran Tari Bagi Siswa Kelas VIII SMP - Kt. Sri Rahayuningsih (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This Classroom Action Research aims to determine the increase in student dance learning outcomes through the application of jigsaw learning methods in the process of learning dance. Collecting data by observation, interviews and documentation. The instruments used were observation sheets, assessment sheets, questionnaire questionnaires, interview guidelines and field notes. The results showed that in the first cycle there were 20% of students not yet completed while the second cycle of completeness reached 100%. It was concluded that the application of the jigsaw type cooperative learning approach in Lancang Kuning dance learning could be used in the practice of Lancang Kuning dance in class VIII.